2022
DOI: 10.1161/jaha.122.025343
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Safety, and Short‐Term Outcomes of Transcatheter Patent Ductus Arteriosus Closure in Premature Infants on High‐Frequency Jet Ventilation

Abstract: Background Prolonged exposure to a hemodynamically significant patent ductus arteriosus (PDA) is associated with major morbidity, particularly in infants born at <27 weeks’ gestation. High‐frequency jet ventilation (HFJV) is a standard of care at our center. There are no data about transcatheter PDA closure while on HFJV. The aim of this study was to assess the feasibility, safety, and outcomes of HFJV during transcatheter PDA closure. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Based on the RBH Cath Lab audit, the median duration of 165 TCPC procedures performed in the Cath Lab was 138 min (IQR 115–165 min), with a minimum of 55 min. These durations align with other facilities reporting median Cath Lab time of 109–121 min, procedure time of 28–32 min, and fluoroscopy time of 4–6 min [ 12 , 13 ]. Therefore, allocating a total case time of up to 3 h is reasonable, considering both the procedure time and transport time between the NICU and the Cath Lab.…”
Section: Anaesthesia Considerationssupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the RBH Cath Lab audit, the median duration of 165 TCPC procedures performed in the Cath Lab was 138 min (IQR 115–165 min), with a minimum of 55 min. These durations align with other facilities reporting median Cath Lab time of 109–121 min, procedure time of 28–32 min, and fluoroscopy time of 4–6 min [ 12 , 13 ]. Therefore, allocating a total case time of up to 3 h is reasonable, considering both the procedure time and transport time between the NICU and the Cath Lab.…”
Section: Anaesthesia Considerationssupporting
confidence: 83%
“…Some ELGAN infants are in the NICU on the High-Frequency Oscillatory Ventilator (HFOV) or High-Frequency Jet Ventilator (HFJV). A study has shown that these ventilators can be used successfully in the Cath Lab for TCPC [ 12 ]. Other authors had suggested a trial off HFOV/HFJV and onto a conventional ventilator for the ease of transport the day before the procedure, only if the patient tolerates it [ 4 ].…”
Section: Anaesthesia Considerationsmentioning
confidence: 99%
“…Ultimately, to expand access to this beneficial procedure, we feel both options are areas of future growth. Additionally, the use of high-frequency ventilation strategies was once thought to be a barrier to performing any definitive closure techniques, but recent evidence has shown that device closure of the PDA in an infant supported by high-frequency jet ventilation is feasible and safe [28]. This could potentially increase the number of patients eligible for device closure, however, it is worth noting that no infants were excluded from device closure in our study due to high-frequency ventilation.…”
Section: Discussionmentioning
confidence: 96%
“…Transcatheter PDA closure is usually performed in the cardiac catheterization laboratory under general anesthesia, with the patient connected to his/her own ventilator. High-frequency jet ventilation, when required, does not compromise the device placement success rate [25]. The procedure is performed using both biplane fluoroscopic and transthoracic echocardiographic guidance.…”
Section: Description Of the Proceduresmentioning
confidence: 99%